2018
DOI: 10.1371/journal.pone.0200735
|View full text |Cite
|
Sign up to set email alerts
|

The importance of stool DNA methylation in colorectal cancer diagnosis: A meta-analysis

Abstract: A large number of tumor-related methylated genes have been suggested to be of diagnostic and prognostic values for CRC when analyzed in patients' stool samples; however, reported sensitivities and specificities have been inconsistent and widely varied. This meta-analysis was conducted to assess the detection accuracy of stool DNA methylation assay in CRC, early stages of CRC (advanced adenoma, non-advanced adenomas) and hyperplastic polyps, separately. We searched MEDLINE, Web of Science, Scopus and Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…In the past few years, significant progress has been made on the sensitivity and specificity of biomarker in stool from CRC patients, demonstrating it as a viable option for CRC screening 18-22. Ahlqist and colleagues reported that during the progression of CRC tumorigenesis, biomarkers release into the stool earlier than into blood 23. Thus, aberrant methylated biomarker screening in stool may help with CRC prevention and early detection.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, significant progress has been made on the sensitivity and specificity of biomarker in stool from CRC patients, demonstrating it as a viable option for CRC screening 18-22. Ahlqist and colleagues reported that during the progression of CRC tumorigenesis, biomarkers release into the stool earlier than into blood 23. Thus, aberrant methylated biomarker screening in stool may help with CRC prevention and early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Assaying molecular markers in stool samples is a promising noninvasive method for screening CRC (42)(43)(44)(45)(46). A recent systematic review demonstrated the eligibility and feasibility of DNA methylation as a noninvasive biomarker in stool samples for the diagnosis of CRC and adenoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, the invasive nature of colonoscopy leads to poor patient compliance. Stool and blood DNA methylation assays based on candidate genes show great diagnostic and prognostic values, but the sensitivities and specificities of the assays vary and are usually inconsistent [78]. In a Chinese cohort study evaluating cfDNA-derived 5hmC analysis in 80 colorectal cancer patients and 90 healthy individuals [45], a total of 989 differentially methylated 5hmC loci in gene bodies were selected as biomarkers to train the machine learning algorithm for cancer classification.…”
Section: Advances In Epigenetic Cancer Biomarker Discovery In Liquid mentioning
confidence: 99%